Alterations of empathy in mothers with a history of early life maltreatment, depression, and borderline personality disorder and their effects on child psychopathology - Dittrich, Katja; Bermpohl, Felix; Kluczniok, Dorothea; Hindi Attar, Catherine; Jaite, Charlotte; Fuchs, Anna; Neukel, Corinne; Herpertz, Sabine; Brunner, Romuald; Winter, Sibylle Maria; Lehmkuhl, Ulrike; Roepke, Stefan; et al. (Psychological medicine, 2020)
Background: Early life maltreatment (ELM), borderline personality disorder (BPD), and major depressive disorder (MDD) have been associated with empathy deficits in different domains. Lack of maternal empathy has also been related to child behavioral problems. As ELM, BPD, and MDD often co-occur, we aimed to identify dissociable effects on empathy due to these three factors. In addition, we aimed to investigate their indirect effects via empathy on child psychopathology. Methods: We included 251 mothers with and without MDD (in remission), BPD and ELM and their children, aged 5-12. We used the Interpersonal Reactivity Index as a measure of empathy on four different dimensions (personal distress, empathic concern, perspective taking, and fantasy) and the Child Behavior Checklist as a measure of child psychopathology. Results: Having included all three factors (ELM, MDD, BPD) in one analysis, we found elevated personal distress in MDD and BPD, and lower levels of perspective-taking in BPD, but no effects from ELM on any empathy subscales. Furthermore, we found indirect effects from maternal BPD and MDD on child psychopathology, via maternal personal distress. Conclusion: The present study demonstrated the dissociable effects of maternal ELM, MDD, and BPD on empathy. Elevated personal distress in mothers with BPD and MDD may lead to higher levels of child psychopathology.